Answer:
343
Step-by-step explanation:
180 is the answer . Just multiply both numbers.
Answer:
1000
Step-by-step explanation:
you look very beautiful btw give me brainliest please ;)
Answer:
x = -2
Step-by-step explanation:
3(-2 - 3x) = -9x - 4 (Given)
3(-2) + 3(-3x) = -9x - 4 (Distributive Property of Equality)
-6 + 9x = -9x - 4 (Simplify)
-6 + 4 -9x= -9x - 4 + 4 (Addition Property of Equality)
-2 + 9x = -9x (Simplify)
-2 +
(Division Property of Equality)
-2 = x (Simplify)
x = -2 (Symmetric Property of Equality)